PENINGKATAN HASIL BELAJAR IPA SISWA KELAS IV DENGAN PENDEKATAN KETERAMPILAN PROSES DI SEKOLAH DASAR - Febriani, Neri; Faridaf, Faridaf; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is motivated by the low of science learning result in class IV SDN 03 Pasar Amping Parak. The purpose of this study is to describe the planning, implementation and improvement of student learning outcomes on science learning by using skills approach for fourth grade students SDN 03 Amping Parak Market Sutera District South Pesisir Regency. The type of research used is classroom action research (PTK). Research subjects are teachers and students of class IV as many as 25 people. The results showed an increase in the results of learning cycle I 72.41 good criteria, cycle II 85.17 with very good criteria, increased 12.76. Means, Approach The process can improve student learning outcomes on science learning in grade IV SDN 03 Amping Parak Market.Keywords: Results of Science Learning, Process Skill